Comparative suitability of the feathers, peripheral blood and spleen tissue samples of chickens for the detection of Marek’s disease virus by polymerase chain reaction (Bangladesh Veterinarian, 2019)
A total of 24 clinical specimens (10 feathers, 8 peripheral bloods and 6 spleens) were collected from 10 suspected outbreaks of Marek’s disease (MD) from Mymensingh, Tangail, Gazipur and Pabna districts of Bangladesh. A polymerase chain reaction (PCR) protocol originally described by Silva (1992) was adopted to detect Marek’s disease virus (MDV) genome in these specimens. All the tested peripheral blood buffy coat samples (100%) were positive for MDV in PCR, while 70% of feather samples and 66.6% of spleen samples were positive. A band of 317 bp size was found in all positive samples. A few samples also yielded additional bands of 185 bp size and/or multiple bands of larger than 317 bp size, indicating the presence of both virulent MDV and the vaccine virus. The study suggests that peripheral blood and feathers from live birds, and feathers from dead birds are the samples of choice for the detection of MDV by PCR.The Bangladesh Veterinarian (2018) 35(1&2): 1-6